Bilateral Total Knee Arthroplasty Guidelines: Are We There Yet? - Vulcano, Ettore; Memtsoudis, Stavros; Della Valle, Alejandro Gonzalez (The Journal of Knee Surgery, 2013)
The proportion of bilateral total knee replacements (BTKR) to unilateral total knee replacement (UTKR) in the United States is increasing. From 1990 to 2004, the use of BTKRs more than doubled for the entire civilian population and almost tripled among the female population. BTKRs can be performed in a single-stage or a staged procedure. Supporters of single-stage BTKR point out its low complication rates, high patient satisfaction, and cost-effectiveness. Others strongly believe that BTKR performed during the same anesthetic session is associated with increased morbidity and mortality. Single-stage BTKR surgery aims at reducing the exposure to repeated anesthesia, total hospitalization and recovery time, and cost, while maintaining patient safety and reducing the negative clinical and functional outcomes observed in patients undergoing UTKR or staged BTKR. This article presents the current concepts and controversies around BTKR surgery based on the authors' body of research and a review of the literature. We also present our institutional guidelines for candidates for single-stage BTKR.
Keywords: bilateral knee replacement; bilateral TKA; bilateral TKA guidelines; single-stage bilateral TKA